ARID2, a Rare Cause of Coffin–Siris Syndrome: A Clinical Description of Two Cases - Wang, Xiaoyan; Wu, Haiying; Sun, Hui; Wang, Lili; Chen, Linqi (Frontiers in Pediatrics, 2022)
Background Coffin-Siris syndrome (CSS) is a multiple congenital anomaly syndrome characterized by coarse facial features, sparse scalp hair, hypertrichosis, and hypo/aplastic digital nails and phalanges. Mutations in the BAF (SWI/SNF)-complex subunits (SMARCE1, SMARCB1, SMARCA4, SMARCA2, ARID1B, and ARID1A) have been shown to cause CSS. People diagnosed with BAF pathway related diseases are increasing, and ARID2 (NM_152641.4) is the least common of these genes. Mutations in the ARID2 gene is the cause for Coffin-Siris syndrome 6 (CSS6). By now only 16 individuals with CSS have been reported to have pathogenic variants in ARID2. Case Presentation In this article, we introduced two individuals with clinical features consistent with CSS6 (Coffin-Siris syndrome 6). This article increases the number of reported cases, provides better phenotypic information for this rare syndrome, and allows everyone to better understand the disease. Conclusion Our observations indicate that ARID2 mutations could have variable phenotypes, even in patients from the same family.